Sekularisasi Pendidikan dan Marginalisasi Nilai Islam: Tantangan Pendidikan Islam di Era Modernisasi dan Globalisasi - Toni Choirul Sidik; Yahya Ashari (Indo Publishing, 2026)
Education is one of the most fundamental elements in shaping human civilization, character, morality, and spiritual awareness. In the Islamic perspective, education is not merely a process of transferring knowledge and developing intellectual abilities, but also a means of cultivating ethical values, spirituality, and noble character based on Islamic teachings. However, the rapid development of modernization, globalization, and technological advancement has significantly transformed the orientation of contemporary education. Modern educational systems tend to emphasize rationality, scientific progress, material achievement, and economic productivity while gradually reducing the role of religion and spirituality in the learning process. This phenomenon is commonly referred to as the secularization of education. The secularization of education has contributed to the marginalization of Islamic values within educational institutions and social life. Islamic teachings are often treated only as complementary subjects rather than as fundamental principles guiding educational objectives and human development. As a consequence, many educational institutions prioritize academic success and professional competence over moral and spiritual formation. This condition has led to various social and moral crises among students, including the decline of ethical behavior, the spread of materialistic and individualistic lifestyles, and the weakening of Islamic identity among younger generations. This article aims to analyze the phenomenon of educational secularization and its implications for the marginalization of Islamic values in modern education. The study also seeks to identify the major factors contributing to this phenomenon and to explore possible solutions for integrating Islamic values into contemporary educational systems. This research employs a library research approach using descriptive and analytical methods. Data were collected from various academic sources, including books, scientific journals, previous research, and scholarly publications related to Islamic education, secularization, modernization, and globalization. The findings of this study reveal that the secularization of education is strongly influenced by the dominance of Western educational paradigms, the dichotomy between religious and secular sciences, and the rapid expansion of global culture through digital media and technology. These factors have weakened the implementation of Islamic values in educational practices and contributed to the emergence of moral degradation and spiritual emptiness among students. Furthermore, the study shows that Islamic education faces significant challenges in maintaining its identity and relevance in the modern era. Therefore, this article emphasizes the importance of reconstructing an integrated educational system that harmonizes scientific knowledge with Islamic moral and spiritual values. The integration of religion and science is considered essential to produce individuals who are intellectually competent, morally responsible, spiritually aware, and socially constructive. In conclusion, Islamic education must not only adapt to the demands of modernity but also preserve its ethical and spiritual foundations in order to contribute positively to the development of a balanced and civilized society.